Difference between revisions of "1951 AHSME Problems/Problem 20"
Mathgeek2006 (talk | contribs) m |
|||
Line 1: | Line 1: | ||
== Problem == | == Problem == | ||
− | When simplified and expressed with negative exponents, the expression <math> (x | + | When simplified and expressed with negative exponents, the expression <math> (x + y)^{ - 1}(x^{ - 1} + y^{ - 1})</math> is equal to: |
− | <math> \textbf{(A)}\ x^{ | + | <math> \textbf{(A)}\ x^{ - 2} + 2x^{ - 1}y^{ - 1} + y^{ - 2} \qquad\textbf{(B)}\ x^{ - 2} + 2^{ - 1}x^{ - 1}y^{ - 1} + y^{ - 2} \qquad\textbf{(C)}\ x^{ - 1}y^{ - 1}</math> |
− | <math> \textbf{(D)}\ x^{ | + | |
+ | <math> \textbf{(D)}\ x^{ - 2} + y^{ - 2} \qquad\textbf{(E)}\ \frac {1}{x^{ - 1}y^{ - 1}}</math> | ||
== Solution == | == Solution == |
Latest revision as of 22:58, 13 March 2015
Problem
When simplified and expressed with negative exponents, the expression is equal to:
Solution
Note that . The answer is .
See Also
1951 AHSC (Problems • Answer Key • Resources) | ||
Preceded by Problem 19 |
Followed by Problem 21 | |
1 • 2 • 3 • 4 • 5 • 6 • 7 • 8 • 9 • 10 • 11 • 12 • 13 • 14 • 15 • 16 • 17 • 18 • 19 • 20 • 21 • 22 • 23 • 24 • 25 • 26 • 27 • 28 • 29 • 30 • 31 • 32 • 33 • 34 • 35 • 36 • 37 • 38 • 39 • 40 • 41 • 42 • 43 • 44 • 45 • 46 • 47 • 48 • 49 • 50 | ||
All AHSME Problems and Solutions |
The problems on this page are copyrighted by the Mathematical Association of America's American Mathematics Competitions.